COMPARATIVE DIAGNOSIS AND TREATMENT METHODS OF TYPE 1 AND 2 DIABETES ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
In this article, the causes and complications of diabetes mellitus and its 1st and 2nd types are described in detail, and the comparative diagnosis of these two types is written.